Green Productivity Techniques for Analyzing Productivity in Agroindustry - Prasetia, Bagus (Tarjih : Agribusiness Development Journal, 2024)
Green Productivity is an approach that integrates productivity efficiency with sustainable practices to achieve a balance between economic growth and environmental protection. This research aims to explore the potential for applying the Green Productivity Method in an agro-industrial context. This research uses a qualitative approach with descriptive methods. The research results show that the application of the Green Productivity method in agro-industry has a positive impact on sustainability. The adoption of green technology, such as energy-saving machines and the use of renewable energy sources, has succeeded in reducing resource consumption and greenhouse gas emissions. Collaboration with research institutions and governments facilitates the integration of sustainable agricultural practices and technological advances. In addition, involving farmers, workers, suppliers and local communities in decision making increases awareness and active participation in implementing sustainable practices. Overall, the results of this research confirm that Green Productivity can be an integral approach to achieving sustainability in the agro-industrial sector by aligning operational efficiency with environmental preservation and social welfare.